2023
DOI: 10.3389/fbuil.2023.1086008
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Himalayan irregular stone masonry buildings for resilient seismic design

Abstract: In the Himalayan region of Nepal, stone masonry has been used for centuries as the primary building material for structures with or without mud mortar. In three distinct remote rural villages, a thorough structural survey of approximately 223 buildings was conducted with an emphasis on their structural irregularities. The thickness of masonry walls frequently varied between floors, which caused mass irregularities. Openings in the front wall of the buildings were not symmetrical in the vertical direction, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…In conclusion, it can be observed that scholars have primarily focused on the research of flood-resistant walls, such as urban movable floodwalls (Miguel et al, 2021;Giacomo and Izzo, 2022) and masonry buildings (Heliová, 2023;Khadka et al, 2023) in rural areas. However, there is a lack of research on the stress characteristics, force transmission mechanism, and flood resistance performance of prefabricated perimeter walls in substations.…”
Section: Introductionmentioning
confidence: 98%
“…In conclusion, it can be observed that scholars have primarily focused on the research of flood-resistant walls, such as urban movable floodwalls (Miguel et al, 2021;Giacomo and Izzo, 2022) and masonry buildings (Heliová, 2023;Khadka et al, 2023) in rural areas. However, there is a lack of research on the stress characteristics, force transmission mechanism, and flood resistance performance of prefabricated perimeter walls in substations.…”
Section: Introductionmentioning
confidence: 98%